An illustrated key and new records of the Afrotropical bark beetle genus Cryphalomimus Eggers (Coleoptera, Curculionidae) - Jordal, B. H. (Zootaxa, 2023)
The Afrotropical genus Cryphalomimus Eggers, 1927 is revised. New distributional records are added, showing a broad but scattered distribution of C. striatus Eggers, 1927. Internal morphological characters for this genus are described here for the first time. An illustrated identification key for the three included species is provided.